Systemic Analysis of The Convergence of The Agricultural Economy in Relation to The Change of Vectors for Achieving Environmental Conditions - Lavinia POPESCU; Adela Sorinela SAFTA (Communications of International Proceedings, 2022)
This paper aims at a systemic analysis of the convergence of the agricultural economy in relation to the change of vectors for achieving environmental conditions. With the increasing consumption needs of healthy agricultural products, the technological performances used in agriculture have triggered the restoration of paradigms in agriculture through the increasing conditionality of consumption, with the variable atmospheric disturbances that tends to major risks in the future. Thus, especially in the field of application of agricultural techniques depending on climate, sustainable monitoring of natural resources, enters into symbiosis through the way the response of good practice in soil treatment, carbon sequestration in soil being relevant from a climate perspective. According to Popescu (2020) points out, an increase in agricultural productivity as a result of the development of agricultural systems would lead to equity by improving the quality of life with the improvement of this agricultural branch and cannot be ruled out in our opinion. The research aimed at analyzing statistical data and the relationship with agricultural technologies applied to the soil to avoid runoff from agricultural sources in groundwater and surface waters in accordance with the Common Agricultural Policy (CAP) which supports the Nitrates Directive by providing direct assistance and development measures rural.
Keywords: Waters; Environmental; Nitrates; Soil.